Cost benefit modeling of AB2X4 (A=Cd; B=Ga; X=S, Se) solar photovoltaic (PV) materials. (August 2019) - Kumar, Pancham; Soni, Amit; Sahariya, Jagrati
Abstract: Present paper focus towards implementation and commercialization of emerging solar PV technology with cost effective manner. Energy band gap, absorption coefficients and module implementation cost for 1KW solar power plant for ternary AB2 X4 (A=Cd; B=Ga; X=S, Se) solar photovoltaic (PV) system is investigated here. All the material related calculations are carried out using density functional theory [1] and cost related calculations by using mathematical expressions. By performing a comparative cost study between proposed materials based solar photovoltaic module and crystalline based solar photovoltaic module we concluded that present material will be cost effectively commercialized as compare to Crystalline Si.